2009
DOI: 10.1111/j.1467-7652.2008.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Root‐selective expression of AtCAX4 and AtCAX2 results in reduced lamina cadmium in field‐grown Nicotiana tabacum L.

Abstract: SummaryTo assess the impact of enhanced root vacuole cadmium (Cd) sequestration on leaf Cd accumulation under a low Cd dose, as generally occurs in agriculture, leaf Cd accumulation was examined in field-grown tobacco plants expressing genes encoding the high-capacity-Cd, tonoplast-localized, divalent cation/H antiporters AtCAX4 and AtCAX2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(35 citation statements)
references
References 26 publications
1
33
0
1
Order By: Relevance
“…Overexpression of AtCAX2 and AtCAX4 in tobacco resulted in Cd accumulation in the roots and a subsequent decrease in the shoots [71]. Four genes that clustered with AtCAX2 and not AtCAX4 (Additional file 13) were identified in N. sylvestris and N. tomentosiformis , suggesting that tobacco CAX gene products orthologous to AtCAX2 and not AtCAX4 may play roles in Cd sequestration in Nicotiana species.…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of AtCAX2 and AtCAX4 in tobacco resulted in Cd accumulation in the roots and a subsequent decrease in the shoots [71]. Four genes that clustered with AtCAX2 and not AtCAX4 (Additional file 13) were identified in N. sylvestris and N. tomentosiformis , suggesting that tobacco CAX gene products orthologous to AtCAX2 and not AtCAX4 may play roles in Cd sequestration in Nicotiana species.…”
Section: Resultsmentioning
confidence: 99%
“…Root‐specific expression of CAX transporters mitigates Cd 2+ content in tobacco leaves (Korenkov et al . 2007, 2009). Future work may also utilise CAX from microalgae such as Chlamydomonas to remediate Cd 2+ ‐polluted freshwater sites (Pittman et al .…”
Section: The Cax Transporters In Biotechnologymentioning
confidence: 99%
“…Further, the various transport systems involved in the accumulation of leaf Cd play different roles. Heterologous expression of AtCAX2 and AtCAX4 in all tissues enhanced Cd accumulation in tobacco leaves [15], whereas selective expression only in roots decreased leaf Cd accumulation [14]. Similarly, A. thaliana plants over expressing AtABCC1 and AtABCC2 in all tissues accumulate higher leaf Cd than controls [20].…”
Section: Introductionmentioning
confidence: 96%
“…To date three types of transporters have been identified that are responsible for sequestering Cd into plant vacuoles. They are CAX-type antiporters, such as CAX2 and CAX4 [14], [15], the Heavy Metal ATPase 3 (HMA3) 1619 and phytochelatin transporters ABCC1 and ABCC2 [20], [21]. Among these, the H + /Cd 2+ -antiporters and HMA3 transport the ionic form of Cd (Cd 2+ ), whereas the phytochelatin transporters transport Cd chelated with phytochelatins [14][21].…”
Section: Introductionmentioning
confidence: 99%